The Effect of Code Switching and Code Mixing of Indonesian Language Teachers on the Language Skills of Class VIII Students of MTs Negeri 2 Padangsidimpuan - Harahap, Rizki Ramadhani; Angraini Lubis, Anita (Jurnal Hata Poda, 2024)
Code switching is a linguistic phenomenon caused by bilingual events and the existence of bilingualism in society. Code mixing is a language event that mixes two or more languages or varieties of languages in a language act. In general, in the teaching and learning process at MTs Negeri 2 Padangsidimpuan, teachers and students always use code switching and code mixing in their speech. This is done so that the teaching and learning process can be understood by both teachers and students. In the realm of education, we can still see code switching and code mixing, especially in the teaching and learning process in schools. This happens because school residents master more than one language. This research aims to determine the effect of Indonesian language teachers' code switching and code mixing on the language skills of class VIII students at MTs Negeri 2 Padangsidimpuan. The theories that support this research consist of sociolinguistics, bilingualism, code switching, code mixing, and indicators of the independent variables in this research. This type of research is field research using a quantitative approach, namely direct research carried out in the field or on respondents. The data collection technique used was a questionnaire. Sampling in this study used a random sampling technique with a sample size of 65 students determined using the Taro Yamane formula. The data analysis method used to obtain the results of the research hypothesis is the multiple linear regression test, t-test and F-test. The results show that there is an influence of Indonesian language teachers' code switching and code mixing on the language skills of class VIII students at MTs Negeri 2 Padangsidimpuan. When carrying out learning activities in class, students more often speak using code switching and code mixing in their speech, whether during presentations or during small discussions when learning is carried out. Keywords: Bilingualism, Code Switching, Code Mixing, Language Skills